Effects of Ultrasonic Nanocrystal Surface Modification on Surface Hardening Mechanism and Wear Behavior of Additively Manufactured High-Manganese Steel - Park, Han-Byeol; Ha, Hyeong-Jin; Cho, Jong-Rae; Shim, Do-Sik (Metals and materials international, 2025)
In this study, high-manganese steel (HMS) fabricated by employing additive manufacturing processes is examined. Samples are classified into three types (13 Mn, 18.5 Mn, and 24 Mn) based on their manganese content. The changes in characteristics resulting from the ultrasonic nanocrystal surface modification (UNSM) treatment applied to as-built HMS are evaluated. The microstructures are refined with an increasing manganese content in as-built HMS; as a result, hardness decreases. The UNSM treatment enhanced the surface characteristics of the material, reducing weight loss and improving wear resistance, particularly for alloys with a low manganese content. Specifically, the UNSM-treated (UNSMed) 13Mn sample exhibits the highest wear resistance, owing to its high surface hardness, which effectively limits wear damage within the severe plastic deformation (SPD) layer. In contrast, UNSMed 18.5Mn and 24Mn samples, which have lower hardness, experience more severe wear damage that extended beyond the SPD layer. Transformation-induced plasticity and twinning-induced plasticity effects are also observed in all wear test samples, along with increased dislocation density near the surface. This suggests that all types of HMS exhibit significant wear resistance, and work-hardening mechanisms effectively inhibit wear damage, even when wear extends beyond the SPD layer. Graphical Abstract